Examination of Wechsler adult Intelligence Scale-Fourth Edition short-form IQ estimations in an outpatient psychoeducational sample. Issue 6 (2nd November 2021) - Merz, Zachary C.; Lace, John W.; Eisenstein, Alexander M.; Grant, Alexandra F.
Abstract: Objective: The Wechsler Adult Intelligence Scale, 4th edition (WAIS-IV) is a commonly utilized cognitive battery across many clinical settings. However, due to various patient variables, an abbreviated assessment of intellectual abilities, may be clinically advantageous to allow for a more thorough assessment of other cognitive domains. The current study represents an attempt to propose additional short-form IQ estimations in an outpatient clinical sample. Methods: We examined archival data from 318 concurrent psychological/psychoeducational evaluations performed within a university clinic ( M age = 28.67; 53.8% women). Thirty-six unique 4-subtest short-form IQ combinations were created to ensure that each WAIS-IV index score was represented by a single subtest. Results: Complete data for the ten core subtests and FSIQ were available for 192 cases. Stepwise regression analyses revealed three short-form combinations that significantly accounted for unique variance in true FSIQ scores in the final model ( R 2 = .981, F [3, 188] = 3257.597, p < .001). Regression-based and prorated FSIQ estimates were calculated, and both methods revealed that approximately 70–75% of participants' FSIQ estimates fell within five Standard Score points of true FSIQ. Conclusion: Results suggest the utility of three derived 4-subtest short-form IQ estimations for use within a clinical sample.